Measurement properties of instruments to assess insight in psychosis: A systematic review protocol - Hadar Hazan; Melissa C. Funaro; Vinod H. Srihari (PLoS ONE, 2025)
Introduction Insight in psychosis, defined as a patient’s awareness and judgment of their mental illness, is a complex and evolving concept. Historically, the absence of insight was considered a defining characteristic of psychosis, but recent decades have seen the development of structured tools for its assessment. This systematic review aims to critically appraise the measurement properties of instruments used to assess insight in individuals with schizophrenia spectrum, bridging the gap between theoretical conceptualization and clinical practice. Methods This protocol is reported following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guidelines. Eligible studies will evaluate instruments measuring insight in psychosis, including self-report, observer ratings, behavioral measurements, and semi-structured interviews. The psychometric properties assessed will encompass reliability, validity, responsiveness, interpretability, and clinical utility. We will include primary quantitative studies published in peer-reviewed journals and available in English. Results Two reviewers will conduct data extraction and quality assessment independently, with discrepancies resolved through consensus or a third reviewer. The COSMIN Risk of Bias checklist and the GRADE approach will be used to evaluate each measure’s methodological quality and overall strength of evidence. Discussion This systematic review will synthesize current evidence on insight measurement in psychosis, providing a comprehensive overview of the strengths and limitations of existing instruments. The findings will inform future research and clinical practice, facilitating the selection of the most appropriate tools for assessing insight and ultimately contributing to improved care for individuals with psychosis. The findings will provide clinicians and researchers with robust tools for assessing insight, ultimately enhancing treatment outcomes for individuals with psychosis.